2016
DOI: 10.1002/cctc.201600245
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to the Mechanism of Fischer–Tropsch Syntheses Arising from Gas Phase NMR and Mass Spectrometry

Abstract: We used 13CO labeling to show that gas‐phase NMR spectroscopy and mass spectrometry are simple tools for mechanistic investigations of the Fischer–Tropsch (FT) reaction. Thus, monodisperse Fe nanoparticles (NPs) react with syngas to form monodisperse iron carbide (FeCx) NPs. As expected, the heating of 13C‐labeled monodisperse FeCx NPs under H2 results in the desorption of the carbide carbons as 13CH4 and, interestingly, restores the initial Fe NPs in terms of size and dispersity. The Fe13Cx NPs catalyze the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…[16][17][18][19] High SAR could be achieved for Fe 0 NPs [20] and their conversion to iron carbide NPs (ICNPs) led to enhanced SAR and better catalytic activity and air stability. [24] Here we show that the carbon content and crystallographic structure of ICNPs can be controlled, impacting directly their effective magnetic anisotropy and by consequence their heating properties,m aking possible the formation of optimized ICNPs displaying exceptionally high SAR. [24] Here we show that the carbon content and crystallographic structure of ICNPs can be controlled, impacting directly their effective magnetic anisotropy and by consequence their heating properties,m aking possible the formation of optimized ICNPs displaying exceptionally high SAR.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…[16][17][18][19] High SAR could be achieved for Fe 0 NPs [20] and their conversion to iron carbide NPs (ICNPs) led to enhanced SAR and better catalytic activity and air stability. [24] Here we show that the carbon content and crystallographic structure of ICNPs can be controlled, impacting directly their effective magnetic anisotropy and by consequence their heating properties,m aking possible the formation of optimized ICNPs displaying exceptionally high SAR. [24] Here we show that the carbon content and crystallographic structure of ICNPs can be controlled, impacting directly their effective magnetic anisotropy and by consequence their heating properties,m aking possible the formation of optimized ICNPs displaying exceptionally high SAR.…”
mentioning
confidence: 76%
“…[21][22][23] Furthermore,w eh ave recently shown that preformed monodisperse Fe 0 NPs (12.5 nm) [14,16] can easily and reversibly incorporate carbon upon reaction with CO and H 2 . [24] Here we show that the carbon content and crystallographic structure of ICNPs can be controlled, impacting directly their effective magnetic anisotropy and by consequence their heating properties,m aking possible the formation of optimized ICNPs displaying exceptionally high SAR. Furthermore,w es how that associated to Ni or Ru, the resulting NPs efficiently catalyze the hydrogenation of CO 2 in adedicated continuous-flow reactor.…”
mentioning
confidence: 76%
“…A synthesis of 15 nm iron carbide NPs (ICNPs) displaying excellent specific absorption rates, and their use for the magnetically induced hydrogenation of carbon dioxide has been recently reported . Inspired from the Fischer‐Tropsch synthesis, the carbidization process is based on the reaction between preformed Fe(0) NPs and a mixture of CO and H 2 at 150 °C ,. These NPs contain more than 80 % of the carbon‐rich Fe 2.2 C crystallographic phase, which was demonstrated to be the key to their enhanced heating power.…”
Section: Figurementioning
confidence: 99%
“…Magnetic induction has recently appeared as an alternative heating source for heterogeneous catalytic reactions . It consists in applying high‐frequency alternating magnetic fields to ferromagnetic materials to release heat through hysteresis losses.…”
Section: Figurementioning
confidence: 99%
“…Magnetic induction has recently appeared as an alternative heating source for heterogeneous catalytic reactions. [1][2][3][4][5][6][7][8][9] It consists in applying high-frequency alternating magnetic fields to ferromagnetic materials to release heat through hysteresis losses. The target temperature is reached within few seconds and the energy is directly transferred inside the material without the need for heating the whole reactor system.…”
mentioning
confidence: 99%